Analisis Faktor yang Berhubungan dengan Status Gizi Anak Balita di Wilayah Pesisir Kecamatan Soropia - Mubarak Mubarak (Halu Oleo University, 2018)
Background: Children under five years old (Balita) are susceptible to health risk and malnutrition. Research Purpose: This research aims to identify the relation of the level of mother’s knowledge, infectious diseases, and the eating habit culture to the nutrirtional status of childrean under five years old in the coastal areas of Kecamatan Soropia. Research Method:The research design using the quantative and cross-sectional analytic. Implemented on October - December 2017 in the coastal areas of Kecamatan Soropia specifically at Sorue Jaya Villlage, Mekar Village, Saponda Darat Village, and Saponda Laut Village. Sampling technique using stratified random sampling with the total of the samples are 93 children under five years old. Data obtained through interviews using instrument quesioner and weight measurement then would be read by using Z-score table to determine the nutritional status (BB/U). Data analysis using chi-square statistical test (0,05). Research Result: Result of the research indicates that the factors related to nutritional status of children under five years old in the coastal areas of Kecamatan Soropia are the level of mother’s knowledge (p-value = 0,003) and infectious diseases (p-value = 0,000). The factors that not relate to the nutritional status is the eating habit culture (p-value = 0,097).Conclusion:Conclusion of the research was that the level of mother’s knowledge and infectious diseases are the factor that related to the nutritional status of children under five years old in coastal areas of Kecamatan Soropia, while eating habit culture is the factor was not.Keywords: nutritional status, childrean under five years old, mother's knowledge, infectious diseases, eating habits culture, coastal areas